Cation diffusion at the interface of composite YAG/Re: LuAG (Re = Nd or Yb) transparent ceramics. Issue 10 (August 2016) - Ma, Chaoyang; Tang, Fei; Zhu, Jiangfeng; Wen, Zicheng; Yu, Yang; Wang, Ke; Du, Miaomiao; Zhang, Jiantao; Long, Jiaqi; Yuan, Xuanyi; Guo, Wang; Cao, Yongge
Abstract: Composite structures of YAG/1 at% Nd-doped LuAG/YAG, YAG/1 at% Nd-doped LuAG and YAG/5 at% Yb-doped LuAG transparent ceramics were successfully fabricated by non-aqueous tape-casting method and vacuum sintering technology. Cation (Y 3+, Lu 3+, Nd 3+, Yb 3+ ) diffusion behavior across the contact boundaries between ytterbium (Yb) or neodymium (Nd) doped lutetium aluminum garnet (LuAG) and un-doped yttrium aluminum garnet (YAG) was studied by the electron probe X-ray micro-analysis (EPMA). The diffusion concentration profile curves were well modeled by Harrison type B kinetics. Curves of concentration vs depth were well fitted by Fick's second low and the log of the average concentration varies as 6/5 power of penetration depth in the diffusion range was demonstrated. Meanwhile, the bulk diffusion coefficient and grain boundary diffusion coefficient were calculated. For YAG/Nd:LuAG transparent ceramic, under an 808 nm diode laser pumping, the 1064 nm continuous wave (C.W.) laser output beam with good quality was achieved.